Relaxin reduces endothelium‐derived vasoconstriction in hypertension: Revealing new therapeutic insights. (31st October 2019) - Leo, Chen Huei; Ng, Hooi Hooi; Marshall, Sarah A.; Jelinic, Maria; Rupasinghe, Thusitha; Qin, Chengxue; Roessner, Ute; Ritchie, Rebecca H.; Tare, Marianne; Parry, Laura J.
Abstract : Background and Purpose: Endothelium‐derived vasoconstriction is a hallmark of vascular dysfunction in hypertension. In some cases, an overproduction of endothelium‐derived prostacyclin (PGI2 ) can cause contraction rather than relaxation. Relaxin is well known for its vasoprotective actions, but the possibility that this peptide could also reverse endothelium‐derived vasoconstriction has never been investigated. We tested the hypothesis that short‐term relaxin treatment mitigates endothelium‐derived vasoconstriction in spontaneously hypertensive rats (SHR). Experimental Approach: Male Wistar Kyoto rats (WKY) and SHR were subcutaneously infused with either vehicle (20 mmol·L −1 sodium acetate) or relaxin (13.3 μg·kg −1 ·hr −1 ) using osmotic minipumps for 3 days. Vascular reactivity to the endothelium‐dependent agonist ACh was assessed in vitro by wire myography. Quantitative PCR and LC‐MS were used to identify changes in gene expression of prostanoid pathways and PG production, respectively. Key Results: Relaxin treatment ameliorated hypertension‐induced endothelial dysfunction by increasing NO‐dependent relaxation and reducing endothelium‐dependent contraction. Notably, short‐term relaxin treatment up‐regulated mesenteric PGI2 receptor (IP) expression, permitting PGI2 –IP‐mediated vasorelaxation. In the aorta, reversal of contraction was accompanied by suppression of the hypertension‐induced increase in prostanoid‐producing enzymes and reduction in PGI2 ‐evoked contractions. Conclusions and Implications: Relaxin has region‐dependent vasoprotective actions in hypertension. Specifically, relaxin has distinct effects on endothelium‐derived contracting factors and their associated vasoconstrictor pathways in mesenteric arteries and the aorta. Taken together, these observations reveal the potential of relaxin as a new therapeutic agent for vascular disorders that are associated with endothelium‐derived vasoconstriction including hypertension.